Treatment of non-carious lesions: Diagnosis, restorative materials and techniques - Caroline Mathias; Laura Nobre Ferraz; Débora Alves Nunes Leite Lima; Giselle Maria Marchi (Universidade Estadual de Campinas, 2018)
Management of non-carious cervical lesions (NCCLs) still is a challenge in clinical practice. The diagnosis is the key to treat these lesions successfully. Aim/Case report: Therefore, the aim of this case report is to describe the diagnosis and treatment of generalized abfraction lesions associated to abrasion lesions of a 43 years old patient and to discuss considerations about the technique and materials to be used appropriately. After the diagnosis, a treatment plan with preventive and restorative approach was elaborated. The occlusal adjustment was performed to distribute the contact points and the patient was instructed in relation to tooth brushing habits. It was also recommended that the patient use a dentifrice with potassium nitrate for the control of sensitivity. For lesions over 1mm deep, the restorative treatment was performed using the self-etching adhesive system and nanohybrid composite by the stratification technique. Unsatisfactory restorations have been replaced. Occlusal splint was done and the patient was instructed to use the device every day overnight. One year after treatment, follow-up was performed. The appearance of new NCCLs was not observed. There was no progression of lesions smaller than 1 mm. There was no loss of restorations. All restorations were fully satisfactory and the patient reported absence of dentin hypersensitivity. Conclusion: The treatment performed besides being aesthetically satisfactory after 1 year resulted in the control of the disease, preventing the appearance of new lesions and guaranteeing a better quality of life to the patient.